Job Seekers ’ Opportunities for the Development of Career Management Skills in Employment Support Programmes - Laškova, Jeļena; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the analysis of instructional theories relevant to jobseekers’ education. The feasibility of the acquisition of career management skills among jobseekers is theoretically grounded by social learning, pragmatism and educational theories, as well as pedagogical approaches of self-learning and learning in action. Jobseeker's learning as a motivated and purposeful activity facilitates the achievement of learning outcomes - to acquire general, vocational and career management skills that will help to find a job in the preferred professional field. The results of the educators survey demonstrates the use of variety of teaching methods, that help to develop career management skills. It is necessary to organize educators’ professional development activities so that in the educational process, working with a target group – jobseekers, they would pay more attention to practical application of career management skills in different situations.